2019
DOI: 10.1038/s41598-019-54096-z
|View full text |Cite
|
Sign up to set email alerts
|

Subtype I (intrinsic) adenomyosis is an independent risk factor for dienogest-related serious unpredictable bleeding in patients with symptomatic adenomyosis

Abstract: We aimed to retrospectively analyze the risk factors of a continuous dienogest (DNG) therapy for serious unpredictable bleeding in patients with symptomatic adenomyosis. This is a retrospective study based on data extracted from medical records of 84 women treated with 2 mg of DNG orally each day between 2008 and 2017. 47 subjects were excluded from the original analyses due to an inadequate subcategorization into subtype I and subtype II and a lack of hemoglobin levels. The influence of various independent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 14 publications
2
36
1
Order By: Relevance
“…These findings may be consistent with clinical data that patients with diffuse adenomyosis suffer from bleeding rather than pain 32 . In addition, Matsubara et al 36 found that type A adenomyosis is related to bleeding and can also strongly cause unexpected bleeding during progestin therapy. On the other hand, type B adenomyosis responds favorably to progestin therapy 36 .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…These findings may be consistent with clinical data that patients with diffuse adenomyosis suffer from bleeding rather than pain 32 . In addition, Matsubara et al 36 found that type A adenomyosis is related to bleeding and can also strongly cause unexpected bleeding during progestin therapy. On the other hand, type B adenomyosis responds favorably to progestin therapy 36 .…”
Section: Resultssupporting
confidence: 86%
“…In addition, Matsubara et al 36 found that type A adenomyosis is related to bleeding and can also strongly cause unexpected bleeding during progestin therapy. On the other hand, type B adenomyosis responds favorably to progestin therapy 36 . Women with type A adenomyosis have less improvement in quality of life after progestin therapy than those with type B adenomyosis, suggesting that there is a difference in the efficacy and safety of progestin therapy between type A and type B adenomyosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well described that dienogest therapy frequently results in irregular bleeding, 3,4 and the bleeding becomes more severe, especially in cases with uterine adenomyosis. 3,5,6 This is the first case report of massive bleeding associated with dienogest therapy that caused a hemorrhagic shock requiring an emergency hysterectomy. In this case, the patient had adenomyosis.…”
Section: Discussionmentioning
confidence: 90%